EFEK PROTEKSI YOGHURT KECIPIR TERHADAP KEJADIAN TUKAK LAMBUNG PADA MENCIT GALUR SWISS YANG DIINDUKSI DENGAN ETANOL - , ZENITA KASIH SETYANI; , dr. Neneng Ratnasari, Sp.PD-KGEH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Gastric ulcer is widespread disease around the world, which is about all segments of society and all ages. The prevalence of gastric ulcers in developing countries reaches 10% and it becomes a major cause of mortality in developing country especially in Indonesia. Yogurt is a fermented milk beverage containing lactic acid bacteria. Lactic acid bacteria are able to provide positive effects for stomach health. To increase the use of local materials, the winged seeds selected in the manufacture of yoghurt. Expected for the future, it may be winged bean yoghurt ingredient complementary foods provide protective effects on the incidence of gastric ulcers. Objective: This study was designed to evaluate the gastro protective effect of winged bean yogurt on ethanol induced gastric ulcers in mice. Methods: Twenty-eight white male Swiss albino mice were divided into four groups. Two groups received winged bean yoghurt (0,4